2010
DOI: 10.1051/apido/2010002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Algerian honeys by palynological and physico-chemical methods

Abstract: -Sixty-six Algerian honeys were sampled for investigation on their palynological and physicochemical properties. Results showed that the total number of pollen grains in 10 g honey ranged from 2.1 × 10 3 to 1.12 × 10 6 . In total 124 pollen species were identified and the main pollen forms were Eucalyptus spp., Olea europaea, Papaver rhoeas, Pimpinella anisum, Carduus sp. and Hedysarum coronarium. Unifloral eucalypt honeys could be distinguished from other honeys from the western Mediterranean region by the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
41
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 15 publications
8
41
1
1
Order By: Relevance
“…The specific conductivity of floral honey should not exceed 0.8 µS/cm (Council Directive 2001), but eucalyptus honey is an exception; therefore, it must be concluded that the resulting value is permitted for this type of honey. Moreover, this value is within the range reported by other authors (up to 1.141 µS/cm) (Chakir et al 2016), although most sources indicate values not exceeding 0.6 µS/cm (Silva et al 2009;Makhloufi et al 2010).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The specific conductivity of floral honey should not exceed 0.8 µS/cm (Council Directive 2001), but eucalyptus honey is an exception; therefore, it must be concluded that the resulting value is permitted for this type of honey. Moreover, this value is within the range reported by other authors (up to 1.141 µS/cm) (Chakir et al 2016), although most sources indicate values not exceeding 0.6 µS/cm (Silva et al 2009;Makhloufi et al 2010).…”
Section: Resultssupporting
confidence: 90%
“…The obtained values of diastase number, especially in the context of the HMF content, may indicate improper production of honey, although there are reports indicating low activity of amylolytic enzymes in eucalyptus honey (about 6°C) (Chakir et al 2016). On the other hand, Makhloufi et al (2010) observed diastase number in eucalyptus honey to range from 8 to 30, HMF content from 6 to 110 mg/kg and invertase activity to range from 1 to 20. In our study, the invertase activity of eucalyptus honey was not considerably lower (0.7).…”
Section: Resultsmentioning
confidence: 71%
“…This is above 65% the minimum limit set by EC regulations [14] in all samples. Makhloufi et al reported Algerian honey with 55.20 to 84.30% reducing sugars [10]. Ouchemoukh et al also reported high reducing sugars of 77.75% in 11 Algerian honeys [12].…”
Section: Resultsmentioning
confidence: 97%
“…HMF (hydroxymethylfurfural) content of different honey samples range from 5.65 ±0.37 to 37.42 ± 0.55 mg/kg (Table 1). Makhloufi et al, BenazizaBouchema and Schweitzer have reported that HMF values were between 0 and 598.8 mg/kg in 140 Algerian honeys [10,19].…”
Section: Resultsmentioning
confidence: 99%
“…However, different methods are combined to determine the geographical and botanical origin of honey, because the composition of honey and its properties are directly dependent on the region of honey origin, environmental conditions, season, method of beekeeping and other factors as evidenced by the large number of scientific publications on this topic. For example, Makhloufi et al (2010) combined palynological, physicochemical and sensory methods, and El Sohaimy et al (2015) combined palynological and physico-chemical methods. Some authors base identification of geographical/botanical origin on the determination of additional mineral composition (Stankovska et al 2008;Uršulin-Trstenjak et al 2015).…”
mentioning
confidence: 99%